PAX3 expression patterns in ocular surface melanocytes - Ulrich, Eva; Kistenmacher, Sebastian; Martin, Gottfried; Schlötzer-Schrehardt, Ursula; Seitz, Berthold; Auw-Hädrich, Claudia; Schlunck, Günther; Reinhard, Thomas; Polisetti, Naresh (Scientific Reports, 2025)
PAX3, a transcription factor essential for neural crest development and melanocyte progenitors, is expressed in various melanocytic tissues. However, its role in ocular surface tissues remains poorly understood. This study investigated the expression patterns of PAX3 in the limbal stem cell niche, specifically in limbal epithelial progenitor cells (LEPC), limbal melanocytes (LM), and limbal mesenchymal stem cells (LMSC). Additionally, PAX3 expression was studied in conjunctival/limbal melanoma specimens. Immunohistochemical analysis revealed predominant PAX3 expression in LM as well in the conjunctival melanocytes, suggesting distinct roles in stem cell regulation and melanocyte maintenance. Notably, PAX3 was significantly upregulated in conjunctival/limbal melanoma tissues compared to healthy counterparts, with expression co-localizing with melanocyte markers (Melan-A, HMB45, SOX10) and the proliferation marker Ki-67 in melanoma cells. These findings suggests that while PAX3 expression is restricted to melanocytes in limbal/conjunctival tissues and its dysregulation may play a crucial role in conjunctival/limbal melanoma development. Further investigation into mechanisms by which PAX3 influences corneal pathophysiology and contributes to conjunctival/limbal melanoma pathogenesis could identify potential therapeutic targets for this aggressive ocular malignancy.
CRIS-Team Scopus Importer:2025-05-02
Keywords: Aniridia; Conjunctival melanoma; Limbal epithelial progenitor cells; Limbal melanoma; Limbal niche cells; Limbal stem cell deficiency; Limbal stem cell niche; Limbal stem cells; Melanocytes; Melanoma; Mesenchymal stromal stem cells; PAX3; PAX6